Analysis of relapsed/refractory Hodgkin lymphoma treated with autologous transplantation: A single-center experience - Vishal Kulkarni; Sulav Sapkota; Girish V Badarkhe; B J Srinivas; Radheshyam Naik (Indian Journal of Medical and Paediatric Oncology)
Introduction: Hodgkin lymphoma (HL) is one of the common lymphomas with high cure rate. Aims: The aim was to study the outcome of relapsed/refractory HL treated with autologous transplantation. Objectives: The objective was to study the overall survival, overall response, and disease-free survival of the relapsed/refractory HL after autologous transplantation. Methods: It was a retrospective study conducted over a period of 8 years in our center using computer-based database and medical records as the data source. Results: A total of 22 patients were diagnosed with relapsed/refractory HL of which majority of cases were male patients (59%) with a mean age of 29 years (range: 15–57 years) and were Stage 4A (40.9%), with nodular sclerosis (54.5%). The overall response rate was 81.8% with 9.1% complete response, 72.7% partial response, and 4.5% stable disease; the overall survival was 77.92 ± 6.65 months, and disease-free survival was 69.66 ± 8.13 months. Conclusion: Autologous stem cell transplant plays an integral role in the treatment of patients with relapsed/refractory Hodgkin lymphoma.